Cold plasma-induced structural and thermal enhancements in marshmallow root mucilage-gelatin aerogels - Marzieh Rownaghi; Mahdi Keramat-Jahromi; Mohammad-Taghi Golmakani; Mehrdad Niakousari (Current Research in Food Science)
Aerogels are highly regarded for their low density and large surface area, attracting significant attention due to their diverse applications. This study explored nitrogen cold plasma's impact on the structure and thermal stability of mucilage-gelatin aerogels (MGA). Aerogels were prepared using marshmallow root mucilage and gelatin in a 1:1 ratio and gelatin-only as a blank under different pH conditions (5 and 7). Rheological and texture analyses identified pH 7 as optimal. Aerogels at pH 7 were then exposed to cold plasma for varying durations (0, 3, and 6 min). Thermogravimetric analysis (TGA), differential thermal analysis (DTA), and X-ray diffraction (XRD) showed enhanced thermal stability and structural changes with increased plasma exposure. Fourier-transform Infrared Spectroscopy (FTIR) revealed functional group changes, and contact angle measurements showed that 3 min of plasma treatment increased hydrophilicity (88.37–82.05°), while 6 min enhanced hydrophobicity in 1:1 MGA (93.27°). BET (Brunauer-Emmett-Teller) analyses of the MGA samples revealed changes in surface area (2.9–4.33 m2/g after 3 min of plasma) and BJH (Barrett-Joyner-Halenda) pore volume (0.004–0.02 cm3/g), with a complex trend over time. This study highlights nitrogen cold plasma's potential to enhance mucilage-based biopolymer aerogels, paving the way for advanced materials via optimized treatments.